DATA FOR ASSESSMENT OF SENIOR SECONDARY SCHOOL BIOLOGY TEACHERS' AND STUDENTS' ATTITUDE TOWARDS COVID-19 IN OYO STATE, NIGERIA (2023)
The World Health Organization's record of 5th July 2023 shows that confirmed global cases and deaths of COVID-19 have scaled up to 767 726 861 and 6 948 764 respectively, while the Nigeria Centre for Disease Control and Prevention (NCDC) had earlier given a situation report on the 26th of February 2023 that there were cumulative numbers of 266 313 confirmed cases and 3 155 deaths from inception of COVID-19 in Nigeria: and 10 350 confirmed cases and 202 deaths in Oyo State. These may have caused heightened anxiety and emotional imbalances that may reflect in the attitude of the citizens of Nigeria across different sectors, including the educational sector, hence the assessment of senior secondary school Biology teachers’ and students’ attitude towards COVID-19 in Oyo State, Nigeria. The study adopted a descriptive research survey design with two research questions, and one research hypothesis. The sample size of the study included 620 Biology students (31 students per school) and 20 Biology teachers (1 teacher per school) from 20 senior secondary schools across 5 Local Government Areas in Oyo State. Two research instruments were used to collect data from respondents, these were Biology Teachers’ Attitude towards COVID-19 Questionnaire (r = 0.83) and Biology Students Attitude towards COVID-19 Questionnaire (r = 0.79). The data were analyzed using descriptive statistics such as per centage (%), mean, and standard deviation; and inferential statistics such as Pearson Product-Moment Correlation Coefficient. This study revealed that senior secondary school Biology teachers and students in Oyo State had positive attitude (with 2.58 weighted mean and 2.52 weighted mean respectively) towards COVID-19; a weak positive relationship that is not significant (r = 0.34; p>0.05) exist between them. Conclusively, the study revealed that teachers’ and students’ participants had positive attitude towards COVID-19. This is an assurance that they were prepared in attitude relating to the disease if there should be a resurgence. However, the relationships in attitude between teachers and students towards the disease was not significant, indicating a gap that needed to be filled.